Transformational Leadership Practices and Their Impact on Students’ Discipline through Organizational Cultural Strengthening in Modern Islamic Boarding Schools in Karawang Regency - Wahidin Wahidin; Fatimah Az Zahro; Achmad Taufik Ismail; Chairil Fajar Hadiansyah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This study examines the influence of transformational leadership on student discipline and the mediating role of organizational culture in a modern Islamic boarding schools in Karawang Regency. This study used a quantitative explanatory survey of 137 students, of which 102 respondents were selected using the Slovin formula and proportional random sampling. Data were analyzed using PLS-SEM with Smart-PLS 4.1.1.6. The results showed that transformational leadership significantly influenced organizational culture (β = 0.687, p < 0.001) and student discipline (β = 0.357, p < 0.001), while organizational culture also significantly influenced student discipline (β = 0.480, p < 0.001). The indirect effect of transformational leadership on student discipline through organizational culture was significant (β = 0.330, p < 0.001; VAF = 48.0%), indicating partial mediation. The model explained 44.9% of the variance in organizational culture and 63.4% of the variance in student discipline. These findings confirm that leadership becomes more effective in strengthening discipline when translated into shared values, routines, and supervisory practices within Islamic boarding schools.